Peningkatan Hasil Belajar Siswa Menggunakan Model PBL Pada Pembelajaran Tematik Terpadu Kelas IV SD - Nadila Ulva; Syafri Ahmad (Universitas Negeri Padang, 2021)
The purpose of this research is to describe the planning, implementation and improvement learning outcomes of students using a problem based learning model in integrated thematic learning in grade IV Elementary School. In this study applying the type of PTK research uses qualitative and quantitative approaches. Where this research was conducted on class IV B SDN 13 Batu Gadang Padang totaling 29 people consisting of 17 male students and 12 female students. The results of the study showed: a). RPP I cycle 86%, cycle II 94,4% b) Implementation on aspects of the teacher the first cycle 82,5%, cycle second 95% c) Implementation on aspects of learners I cycle 85%, cycle II 96,4% d) Learning outcomes students in first cycle obtaines an average score of 72,24, cycle II 83,32. So that, the problem based learning model can improve student learning outcomes in integrated thematic learning in class IV B SDN 13 Batu Gadang Padang.